Isolation and characterization of lactic acid bacteria from Apis mellifera and their potential as antibacterial using in vitro test against growth of Listeria monocytogenes and Escherichia coli - Indriana Putri; Siti Nur Jannah; Susiana Purwantisari (NICHE Journal of Tropical Biology, 2020)
Food spoilage can caused by pathogenic bacteria and can cause disease (food-borne pathogens). Foods that are vulnerable to pathogenic bacteria are foods that contain lots of protein, such as meat, milk and eggs. Listeria monocytogenes and Escherichia coli are commonly found in fresh meat. The solution for the problem is microbiological preservation by using Lactic Acid Bacteria (LAB). The purpose of this study is to isolate LAB from Apis mellifera honey, find out its characteristics, and test for antibacterial growth of L. monocytogenes and E. coli. LAB have been isolated with pour plate. Morphological characterization have been done by observing the colonies macroscopically and microscopically. LAB have been enumerated by Total Plate Count (TPC). Antibacterial Test have been done by well diffussion method. Experimental design was using Completely Randomized Factorial Design (CRFD). Statistical analysis have been done by univariate test with SPSS 16.0. 1st factor is LAB, 2nd factor is pH of supernatant and 3rd factor is pathogenic bacteria. Total 9 isolates of LAB were obtained from A. mellifera honey. LAB population is 9.6 x 105 CFU/mL. The result of screening LAB antibacterial assay is 2 potential isolates, they are MA 3 and MA 4. The best supernatant of LAB that could inhibit the growth of L. monocytogenes and E. coli is MA 3 with average diameters 12,05 mm and 12,07 mm. Pathogenic bacteria that is more sensitive is E. coli, because of the antibacterial compound from LAB is composed by organic acid that can break down the outer membrane and lower the pH, so pathogenic bacterial cannot be adapted to acidic environment.